Perbandingan Sistem Wakaf Sebagai Implementasi Kebijakan Distribusi Sosial (Studi Kasus: Arab Saudi Dan Malaysia) - Afni Regita Cahyani Muis; Mia Utami Putri; Zahra Amalia; Nanda Putri Khalifah; Faatimah Faatimah (Hasanuddin Journal of International Affairs, 2023)
This article will explain the comparison of waqf systems in Malaysia and Saudi Arabia. Each country has a different waqf management system that supports social distribution policies. Malaysia is managed by the State Islamic Religious Council, as Malaysia is a federal country and each state has a Waqf Management Committee to manage waqf assets. Saudi Arabia is managed by a special institution called the Higher Waqf Council, chaired by the Minister of Hajj and Waqf, with the authority to distribute waqf assets according to the mandate given by the waqif. This study uses a comparative method by analyzing two objects which then result in similarities and differences in the waqf system to find social distribution policy factors and their implementation. This study uses a qualitative-descriptive method with secondary analysis, namely using secondary data such as journals and official websites. The results of this study show that the management of waqf is different in each organization in their respective countries and has different authorities, but the results still make waqf as one of the policies made by the government for their country.   Artikel ini akan menjelaskan perbandingan sistem wakaf di negara Malaysia dan Arab Saudi. Setiap negara memiliki sistem pengelolaan wakaf berbeda yang mendukung kebijakan distribusi sosial. Malaysia dikelola oleh Dewan Agama Islam Negara, karena Malaysia adalah negara federal dan setiap negara memiliki SIRC untuk mengelola wakaf. Arab Saudi yang dikelola oleh lembaga khusus yang disebut Majelis Tinggi Wakaf diketuai oleh Menteri Haji dan Wakaf, dengan kewenangan untuk mendistribusikan aset wakaf sesuai mandat yang diberikan oleh wakif. Penelitian ini menggunakan metode komparatif dengan menganalisis dua objek yang kemudian menghasilkan persamaan dan perbedaan sistem wakaf untuk menemukan faktor-faktor kebijakan distribusi sosial dan implementasinya. Penelitian ini menggunakan metode kualitatif-deskriptif dengan secondary analysis, yaitu menggunakan data sekunder, seperti jurnal-jurnal dan official website. Hasil dari penelitian ini adalah bahwa dalam pengelolaan wakaf yang dikelola oleh masing-masing organisasi di negaranya dan memiliki kewenangan yang berbeda-beda namun hasilnya tetap menjadikan wakaf sebagai salah satu kebijakan yang dibuat oleh pemerintah untuk negaranya.